Functional significance of O-GlcNAc modification in regulating neuronal properties - Hwang, Hongik; Rhim, Hyewhon (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2018)
Post-(t)ranslational modifications (PTMs) covalently modify proteins and diversify protein functions. Along with protein phosphorylation, another common PTM is the addition of O-linked beta-N-acetylglucosamine (O-GlcNAc) to serine and/or threonine residues. O-GlcNAc modification is similar to phosphorylation in that it occurs to serine and threonine residues and cycles on and off with a similar time scale. However, a striking difference is that the addition and removal of the O-GlcNAc moiety on all substrates are mediated by the two enzymes regardless of proteins, O-GlcNAc transferase (OGT) and O-GlcNAcase (OGA), respectively. O-GlcNAcylation can interact or potentially compete with phosphorylation on serine and threonine residues, and thus serves as an important molecular mechanism to modulate protein functions and activation. However, it has been challenging to address the role of O-GlcNAc modification in regulating protein functions at the molecular level due to the lack of convenient tools to determine the sites and degrees of O-GlcNAcylation. Studies in this field have only begun to expand significantly thanks to the recent advances in detection and manipulation methods such as quantitative proteomics and highly selective small-molecule inhibitors for OGT and OGA. Interestingly, multiple brain regions, especially hippocampus, express high levels of both OGT and OGA, and a number of neuron-specific proteins have been reported to undergo O-GlcNAcylation. This review aims to discuss the recent updates concerning the impacts of O-GlcNAc modification on neuronal functions at multiple levels ranging from intrinsic neuronal properties to synaptic plasticity and animal behaviors. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: LONG-TERM DEPRESSION; SYNAPTIC PLASTICITY; MODIFIED PROTEINS; ALPHA-SYNUCLEIN; LINKED GLCNAC; NUTRIENT REGULATION; GENE-EXPRESSION; AMPA RECEPTORS; AMYLOID-BETA; TAU-PROTEIN